2023
DOI: 10.3233/jifs-221720
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid machine learning approach for traffic sign detection using CNN-GRNN

Abstract: The traffic signal recognition model plays a significant role in the intelligent transportation model, as traffic signals aid the drivers to driving the more professional with awareness. The primary goal of this paper is to proposea model that works for the recognition and detection of traffic signals. This work proposes the pre-processing and segmentation approach applying machine learning techniques are occurred recent trends of study. Initially, the median filter & histogram equalization technique is ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One of the key insights gleaned from this research is the significant impact of CNN architecture on the performance of traffic sign recognition models. As demonstrated in previous studies [33], the hierarchical feature extraction capabilities of CNNs enable the automatic learning of discriminative features from raw image data, thereby facilitating accurate classification of traffic signs [34]. By leveraging multiple convolutional layers followed by fusion, flatten, dropout, and dense layers, the proposed CNN architecture effectively captures spatial dependencies and semantic information inherent in traffic sign images, leading to superior recognition performance.…”
Section: Discussionmentioning
confidence: 88%
“…One of the key insights gleaned from this research is the significant impact of CNN architecture on the performance of traffic sign recognition models. As demonstrated in previous studies [33], the hierarchical feature extraction capabilities of CNNs enable the automatic learning of discriminative features from raw image data, thereby facilitating accurate classification of traffic signs [34]. By leveraging multiple convolutional layers followed by fusion, flatten, dropout, and dense layers, the proposed CNN architecture effectively captures spatial dependencies and semantic information inherent in traffic sign images, leading to superior recognition performance.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, machine learning methods are also used in predicting traffic crash severity [23], classifying traffic conditions [130], and detecting traffic sign [131]. However, the commonly-used models are different in different research fields, such as Artificial Intelligence method in ITS field [132] and Artificial neural network approach in predicting road traffic accidents [133].…”
Section: Discussionmentioning
confidence: 99%
“…performed the bibliometric analysis on traffic flow prediction and found that the USA and China are the countries with most works published on socially sustainable transport [16], Autonomous Vehicles [129], or subgrade stability and reinforcement with special soil [25]. In addition, machine learning methods are also used in predicting traffic crash severity [23], classifying traffic conditions [130], and detecting traffic sign [131]. However, the commonly‐used models are different in different research fields, such as Artificial Intelligence method in ITS field [132] and Artificial neural network approach in predicting road traffic accidents [133].…”
Section: Discussionmentioning
confidence: 99%